The Readiness of Malaysian Employees in Understanding Integrity Based on the Model ‘Al-Khauf Wa Ar- Raja’ - Mohd Sham, Kamis; Muhammad Khalid, Osman; Muhammad Nazir, Alias; Nik Abdul Rahim, Nik Abdul Ghani; Luqman Hakim, Satiman (Elite Scientific Publications, Pakistan, 2024)
This study aims to investigate the readiness of Malaysian Employees to understand integrity based on the Model Al-Khauf Wa Ar-Raja. The objective is, a) to identify the readiness of the Malaysian Employees of the Ministry of Communications, Putrajaya, Malaysia in enforcing the principle of integrity, b) to explore the approach of monitoring by the Ministry as mentioned in managing indiscipline matters at the workplace among the employees. The authors preferred quantitative data for conducting Research Question 1 (RQ1) and qualitative data for conducting Research Question 2 (RQ2). The finding of RQ1 was obtained from the respondents (N= 200) via a questionnaire. RQ1. How to identify the readiness of the Malaysian Employees of the Ministry of Communications, Putrajaya, Malaysia in enforcing the principle of integrity? Meanwhile, RQ2 was obtained saturated data via an interview with the participants (N=3). RQ2. What is the approach of monitoring implemented by the Ministry of Communications Putrajaya, Malaysia in managing indiscipline matters at the workplace among the employees? The finding of RQ1 consists of five perspectives; a) Integrity in a workplace, 2.48 moderate level; b)Monitoring in the practice of integrity, 2.4 moderate level; c) Each organization has its circular, 2.23 low level; d) Pure value perseverance elements, 2.6 moderate level; and; e) Educating individual personalities of taqwa, 2.34 moderate level. RQ2, the approach of monitoring implemented by the Ministry of Communications Putrajaya, Malaysia in managing indiscipline matters at the workplace among the employees as majority answer such as; a) Instilling awareness integrity in a workplace; b) Being trustworthy in supporting our organization's values sincerely; and e) Avoiding lack of integrity among employees including turning a blind eye to an unethical behaviour or when they are modelling an unethical behaviour. The contribution of this study, such as the model development of the integrity for Malaysian Civil Servants.